Comparative Analysis of Advantages and Disadvantages of the Criteria Considered by Technology Surveillance Models - Ardiles-Briones, M (UNIV SANTIAGO CHILE, FAC TECNOLOGICA, 2021)
This article presents a comparison analysis of the advantages and disadvantages of the different criteria considered by technology surveillance models. For this purpose, some models of technological surveillance are described, to later analyze the main criteria used in the various phases of this methodology. This analysis will simplify decision-making regarding which model to adopt for the incorporation of a technology surveillance methodology in organizations. As a result, various characteristics that organizations must take into consideration are exposed to effectively use a technology surveillance model.